Analysis And Design Of E-Commerce (B2B) With The Technology Acceptance Model Method At PT. Global Pharma Indonesia - Ananda Yulianto Putra; Ardie Halim Wijaya (Tech-E, 2020)
Technological advances make competition more competitive so companies are competing in introducing and selling goods by utilizing technology, one of the most rapid technological advances is the internet, the increasing number of internet users has a positive impact on e-commerce. Therefore e-commerce can provide information on goods, facilitate ordering of goods and is not limited by time and distance, to determine the acceptance of technology users, then the Technology Acceptance Model method is used with variables of perceived ease of use, attitude toward using, perceived usefulness, actual usage, behavioral intention. The research sample of 26 employees. Based on the results of the linear analysis noted that attitude toward using can be explained by variations in perceived ease of use, behavioral intention, and perceived usefulness of 52,5 percent, while actual usage can be explained by variations in perceived ease of use, perceived of usefulness, and behavioral intention of 72,2 percent and the remaining 47,5 percent and 27,8 percent are explained by other factors outside the model.